A novel continuously variable transmission with logarithmic disc generatrix. (November 2015) - Li, Qingtao; Li, Hua; Yu, Deping; Yao, Jin
Abstract: Although the toroidal continuously variable transmission (CVT) is an ideal drive mode for internal combustion engine vehicles, its total mechanical efficiency is limited due to the spin losses caused by the different speed distribution in the contact area of the toroidal CVTs. To overcome this shortcoming as well as improve the mechanical efficiency, this paper proposes a novel logarithmic CVT by replacing its circular generatrix with a logarithmic generatrix. Equations for its transmission ratio and half cone-angle, which are two essential design parameters, are derived and their ranges are suggested. It turns out that this design introduces drawbacks of reduced transmission ratio range and increased complexity of the control mechanism. However, this design theoretically offers no spin loss in the full transmission ratio range. A computational method has been proposed to compute the mechanical efficiency of the logarithmic CVT. Computational results show that the logarithmic CVT has higher and more stable efficiency than that of the half toroidal CVT. Highlights: A novel CVT is proposed which can theoretically offer the no spin traction drive in a full transmission ratio range. Equations for the transmission ratio and half cone-angle are derived and their ranges are suggested. The new CVT is proved to have higher and more stable efficiency than that of the half toroidal CVT.